GE_GERICHTE C/25535/2013 vom 16. Oktober 2015 - GE Cour de justice (2015)
PROTECTION DE L'UNION CONJUGALE; DROIT DE GARDE; OBLIGATION D'ENTRETIEN; AVANCE DE FRAIS; CONJOINT | CPC.261; CC.176.3; CC.176.1.1